2021
DOI: 10.1111/jpn.13639
|View full text |Cite
|
Sign up to set email alerts
|

Oregano essential oil showed limited effects on pigs' carcass quality and haematology whereas a transcriptome analysis revealed significant modulations in the jejunum and the ileum

Abstract: Pig production depends on a health and performance balance. An approach to improve intestinal health is the oregano essential oil (OEO) supplementation within a conventional diet. Intestinal integrity regulating effects, for example gene expression, of some feed ingredients are important key factors for that balance. We hypothesized that OEO affects the expression of genes associated with pigs’ intestinal integrity. In four trials, a total of 86 pigs have been used. From weaning, the ‘treated’ group (n = 42) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 123 publications
0
3
0
Order By: Relevance
“…Oregano oil supplementation upregulated the mRNA expression of intestinal barrier gene ZO-1 and Claudin-1 in the duodenum and Claudin-1 in the ileum of Eimeria -challenged broilers, which was consistent with the findings from Ruan et al (2021) . The upregulation of tight junction in the epithelial barrier was also reported in colorectal cancer mice model ( Leong et al, 2022 ), female pigs ( Hofmann et al, 2022 ), Escherichia coli -challenged mice ( Zhao et al, 2022 ), and colitis mice ( Raka et al, 2023 ). It is remarkable how essential oil interacts with the monolayer of enterocytes, probably due to their antioxidant capacity ( Toschi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 74%
“…Oregano oil supplementation upregulated the mRNA expression of intestinal barrier gene ZO-1 and Claudin-1 in the duodenum and Claudin-1 in the ileum of Eimeria -challenged broilers, which was consistent with the findings from Ruan et al (2021) . The upregulation of tight junction in the epithelial barrier was also reported in colorectal cancer mice model ( Leong et al, 2022 ), female pigs ( Hofmann et al, 2022 ), Escherichia coli -challenged mice ( Zhao et al, 2022 ), and colitis mice ( Raka et al, 2023 ). It is remarkable how essential oil interacts with the monolayer of enterocytes, probably due to their antioxidant capacity ( Toschi et al, 2022 ).…”
Section: Discussionmentioning
confidence: 74%
“…PTBP1 (polypyrimidine tract binding protein 1) is an RNA-binding protein, a specific inhibitor of mRNA splicing in the mammalian nervous system ( Medina et al, 2011 ). CFD promotes adipocyte differentiation and promotes adipogenesis ( Song et al, 2016 ), and GRIN3B affects beef quality ( Hofmann et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to improve serum antibody reaction, tea tree oil is shown to increases liver IL-10 and decreases the IL-1β and TNF-α concentrations (Wang et al 2021b ). Hofmann et al ( 2022 ) have demonstrated that oregano essential oil can increase expressions of TJP1 (encoding tight junction protein ZO-1), Akt3, interferon signaling and CCL21 in the porcine small intestine (Hofmann et al 2022 ). Capsicum oleoresin or turmeric oleoresin supplement up-regulates the gene signature of immune activation ( C1QA, C5, CCL25, CD46, CFB, and FCN2 ), cell membrane integrity, and tight junctions in the porcine ileum mucosa; while garlic extract increases the expression of genes involved in fatty acid biosynthesis, defense response, and oxidation reduction in pigs (Liu et al 2014c ).…”
Section: Alternatives To Antibiotics In Pig Production: Modulating Th...mentioning
confidence: 99%